2021
DOI: 10.4103/jfmpc.jfmpc_386_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge about osteoporosis risk factors among adults above 40 years of age in Hafar Al-Batin Region, Saudi Arabia

Abstract: Background: Osteoporosis is a growing public health issue that is prevalent among the Saudi Arabian population. Several risk factors for the disease have been identified and could be modified using preventive strategies, including increasing awareness about the disease in susceptible individuals. Methods: A cross-sectional study was conducted using interview-based questionnaires to evaluate knowledge of osteoporosis risk factors in a sample of 513 Saudi participants att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
1
2
Order By: Relevance
“…The higher osteoporosis-related knowledge among female participants was similar to several prior studies in Saudi Arabia [32,33]; Malaysia [31]; Canada [34], and Southern United States [35]. However, in the study by Alrashidy et al, 2021, they reported conflicting results, as it was found that males had better knowledge of osteoporosis than females. These disparities could be attributed to participants' basic data differences, such as educational level and employment status.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The higher osteoporosis-related knowledge among female participants was similar to several prior studies in Saudi Arabia [32,33]; Malaysia [31]; Canada [34], and Southern United States [35]. However, in the study by Alrashidy et al, 2021, they reported conflicting results, as it was found that males had better knowledge of osteoporosis than females. These disparities could be attributed to participants' basic data differences, such as educational level and employment status.…”
Section: Discussionsupporting
confidence: 82%
“…These disparities could be attributed to participants' basic data differences, such as educational level and employment status. In the current study, 65.3% of the participants had a higher education compared to 14.8% in the study by El-Rachidi et al Moreover, only 17.1% of the participants were not working compared to 72% in the El-Rachidi et al study [36].…”
Section: Discussioncontrasting
confidence: 70%
“…In our study, 92.2% of participants reported that osteoporosis increases the incidence of fractures. This was higher than the results reported in another study, as three-quarters of the respondents in this analysis agreed that osteoporosis and fractures are related (Alrashidy, 2021) expected to experience a clinical fracture (Johnell and Kanis, 2006). A sensible and successful treatment for osteoporosis in peri-and early postmenopausal women is hormone replacement therapy (Gambacciani and Levancini, 2014).…”
Section: Resultscontrasting
confidence: 65%
“…Individuals with a higher level of knowledge and understanding about osteoporosis are supposed to be more likely to recognize the value of screening services and proactively seek them out. One study conducted in Saudi Arabia found that more than one-third of the participants had moderate or poor knowledge of osteoporosis [14]. Increased education and awareness campaigns can contribute to improving this motivator and consequently enhance screening uptake.…”
Section: Introductionmentioning
confidence: 99%